Physiotherapy in frozen shoulder syndrome - literature review - Korabiusz, Katarzyna; Wawryków, Agata; Niedzielska, Mirela; Janik, Inga; Fabian- Danielewska, Anna (Journal of Education, Health and Sport, 2017)
Introduction: The frozen shoulder syndrome is seen as civilization illness. A significant amount of people suffer from it. The frozen shoulder syndrome is one of the most frequent dysfunctions of pectoral girdle. It is seen as a second frequent reason for visits at General Practicioner. There are three stages of this illness, there are a lot of symptoms, but one that occurs most commonly is pain. This illness can be completely curable. Research goal: Goal of this dissertation is a review of literature about available physiotherapy methods used in frozen shoulder syndrome. Conclusion: Kinesiotherapy, kinesiotaping, criotherapy, LASER, Traebert’s currents, iontophoresis, magnetic fields, ultrasounds, massage, manual therapy and combined therapy are effective physiotherapy methods used in treating frozen shoulder syndrome. Those methods reduce pain indispositions and increase range of movement in shoulder joint.